Essential Emergency Surgical Care in Remote Hilly Districts of Karnali - A Cross-Sectional Survey - Giri, Praveen Kumar; Panta, Prem Prasad; Thapa, Niresh (Journal of Karnali Academy of Health Sciences, 2020)
Background: Remote hilly areas of Karnali Province has one in all the very best burdens of surgically treatable conditions within the world and therefore, the highest unmet need. The first objective of our study was to gauge the capacity of first-referral health facilities in remote districts of Karnali Province to perform basic surgical procedures. The aim is to assess the status of Essential Emergency Surgical Care in remote hilly districts of Karnali region of Nepal. Method: The screening Tool was Situational Analysis to Assess Emergency and Essential Surgical Care, to spot the health facility’s capacity to perform basic surgical (including obstetrics and trauma) and anesthetic procedures by investigating four categories of data: human resources, infrastructure, equipment and interventions available. The tool interrogated the supply of eight sorts of care providers, 35 surgical interventions and 67 items of apparatus. Results: on the average, 72.83% of all admissions required either minor or major surgical interventions. Oxygen supplies, electrical power backup, running water, blood bank, hospital guidelines were inconsistent. Only 1 Hospital have trained Surgeons, Anesthesiologist and Obstetrician/Gynecologist. Only 1 hospital can perform around 97.1% of procedures. Conclusion: The capacity for essential surgery is severely limited in Karnali region of Nepal. Limitations was seen in basic equipment, human resources, infrastructure, and supplies.